The consistency of Federalist Society-affiliated U.S. supreme court justices. - Tim Komatsu; Paul M Collins (PLoS ONE)
The U.S. Supreme Court has recently undergone a dramatic turn to the right, fundamentally reshaping law and politics in America. In this article, we examine one reason for this shift: the increasingly prominent role of the Federalist Society in the conservative legal movement. An analysis of almost 25,000 votes of Supreme Court justices from 1986-2022 shows that justices affiliated with the Federalist Society are about 10 percentage points more likely to cast a conservative vote than their non-affiliated counterparts, and the voting behavior of Federalist Society-affiliates is more ideologically consistent than non-affiliated justices. Because justices in the contemporary era serve on the Court for an average of about a quarter century, these findings indicate that we are likely to see the Court's conservative justices - who are all Federalist Society-affiliates - continue to advance the conservative legal movement's agenda for decades to come.